The Influence of Workload, Work Stress, Job Satisfaction, Work Discipline, and Compensation on Turnover Intention Among Nurses in Purbalingga Regency - Sutaryo, Sutaryo; Santoso, Suryo Budi; Astuti, Herni Justiana; Kusbandiyah, Ani (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research aims to determine the effect of workload, work stress, job satisfaction, work discipline, and compensation on turnover intention among nurses in Purbalingga Regency. The type of research used in this research is quantitative research, the data source used is primary data with a data collection method in the form of a survey using a questionnaire. The population in this study were all nurses in Purbalingga Regency, totaling 471 people. The sample in this study amounted to 216 people using purposive sampling. The instrument test requirements used are validity and reliability tests. The data analysis method uses multiple linear regression and the hypothesis tests used are the T-test. The results of this study partially state that Workload has a positive effect on nurses' Turnover Intention in Purbalingga Regency, Work Stress has a positive effect on nurses' Turnover Intention in Purbalingga Regency, Job Satisfaction has a negative effect on nurses's Turnover Intention in Purbalingga Regency, Work Discipline has a negative effect on nurses's Turnover Intention in Purbalingga Regency, Compensation has an negative effect on nurses' Turnover Intention in Purbalingga Regency.